The implications of socialization and integration in supply chain management - Cousins, Paul D.; Menguc, Bulent (Journal of Operations Management, 2006)
AbstractFor many years, firms have been organizing supplier conferences, conducting on‐site visits, and talking about the concept of joint buyer/supplier teams. It is believed that the implementation of these concepts enhances inter‐firm relationships. Furthermore, as firms move towards closer and more integrated supply chains it is argued that socialization is an increasingly important mechanism in facilitating and enhancing the supply integration process. This paper has taken these activities and embedded them in the theory of ‘socialization’ and supply chain integration. The authors propose and test a model on how buyers can use the concepts of supply chain integration and socialization to achieve improved supplier communication and operational performance, and therefore, to improve the buyer's perceived level of the supplier's contractual conformance. The findings reveal that socialization is essential for the development of any significant business relationship and the enhancement of a supply integration strategy.